Romantic Love vs. Drug Addiction May Inspire a New Treatment for Addiction - Zou, Zhiling; Song, Hongwen; Zhang, Yuting; Zhang, Xiaochu (Frontiers in Psychology, 2016)
Drug addiction is a complex neurological dysfunction induced by recurring drug intoxication. Strategies to prevent and treat drug addiction constitute a topic of research interest. Early-stage romantic love is characterized by some characteristics of addiction, which gradually disappear as the love relationship progresses. Therefore, comparison of the concordance and discordance between romantic love and drug addiction may elucidate potential treatments for addiction. This focused review uses the evidences from our recent studies to compare the neural alterations between romantic love and drug addiction, moreover we also compare the behavioral and neurochemical alterations between romantic love and drug addiction. From the behavioral comparisons we find that there are many similarities between the early stage of romantic love and drug addiction, and this stage romantic love is considered as a behavioral addiction, while significant differences exist between the later stage of romantic love and drug addiction, and this stage of romantic love eventually developed into a prosocial behavior. The neuroimaging comparisons suggest that romantic love and drug addiction both display the functional enhancement in reward and emotion regulation network. Except the similar neural changes, romantic love display special function enhancement in social cognition network, while drug addiction display special dysfunction in cognitive control network. The neurochemical comparisons show that there are many similarities in the dopamine (DA) system, while significant differences in oxytocin (OT) system for romantic love and drug addiction. These indicate that the functional alterations in reward and emotion regulation network and the DA system may be the neurophysiological basis of romantic love as a behavioral addiction, and the functional alterations in social cognition network and the OT system may be the neurophysiological basis of romantic love as a prosocial behavior. It seems that the OT system is a critical factor for the development of addiction. So we then discuss strategies to treat drug addiction with OT, and suggest that future research should further investigate OT system interventions aiming to improve cognitive control and/or social cognition functions, in order to develop strategies designed to more effectively treat drug addiction.